The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijms232415863
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of CRISPR-Cas Gnome Editing in C. elegans

Abstract: CRISPR-Cas allows us to introduce desired genome editing, including mutations, epitopes, and deletions, with unprecedented efficiency. The development of CRISPR-Cas has progressed to such an extent that it is now applicable in various fields, with the help of model organisms. C. elegans is one of the pioneering animals in which numerous CRISPR-Cas strategies have been rapidly established over the past decade. Ironically, the emergence of numerous methods makes the choice of the correct method difficult. Choosi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Various genetic models, such as zebrafish, Caenorhabditis elegans, and Drosophila, also benefits from CRISPR's technology and genome modification. It is worthwhile to mention that different studies have reported hereditary germinal modification, the introduction of high efficiency of specific mutations, and transgenic, tissue-specific editing in flies (33)(34)(35)(36)(37)(38), fish (39)(40)(41)(42)(43)(44)(45), and worms (46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56).…”
Section: Crispr-cas9 and Lower Organismsmentioning
confidence: 99%
“…Various genetic models, such as zebrafish, Caenorhabditis elegans, and Drosophila, also benefits from CRISPR's technology and genome modification. It is worthwhile to mention that different studies have reported hereditary germinal modification, the introduction of high efficiency of specific mutations, and transgenic, tissue-specific editing in flies (33)(34)(35)(36)(37)(38), fish (39)(40)(41)(42)(43)(44)(45), and worms (46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56).…”
Section: Crispr-cas9 and Lower Organismsmentioning
confidence: 99%
“…The CRISPR-Cas9 system has been successfully adopted in various nematode species, including the classical model C. elegans, the necromenic nematode Pristionchus pacificus, the mammalian parasite Strongyloides stercoralis, and other non-model species, such as Aunema , Oscheius, and Panagrolaimus (Adams et al, 2019; Castelletto & Hallem, 2021; Dockendorff et al, 2022; Hellekes et al, 2023; Hiraga et al, 2021; H.-M. Kim et al, 2022; Lok, 2019). In these successful cases, either plasmid encoded Cas9 and guide RNAs or Cas9 RNP were delivered through microinjection into the gonad of a hermaphrodite or a female nematode.…”
Section: Introductionmentioning
confidence: 99%